2020
DOI: 10.1519/jsc.0000000000003490
|View full text |Cite
|
Sign up to set email alerts
|

In-Season Session Training Load Relative to Match Load in Professional Ice Hockey

Abstract: In-season session training load relative to match load in professional ice hockey. J Strength Cond Res 36(2): 486-492, 2022-The aim of this study was to describe match load and intensity across player positions and match periods, the distribution of pregame training load and intensity over training days before a match, by player position, and the cumulative weekly training load over a season. Fifty professional ice hockey players, which at one time or another were part of the roster for the Laval Rocket during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 32 publications
2
35
4
Order By: Relevance
“…All four cumulative workload measures (i.e., PL, SL, EE, and HFS) were significantly higher in matches compared to training, indicating that matches required higher volumes of both total and high-intensity work. PL•min -1 and SL•min -1 were higher in training, which is in contrast to previous reports of higher measures of work rate in competition compared to training (Allard et al, 2020;. This discrepancy may be reflective of population differences or philosophical differences related to the overall tempo of training design.…”
Section: Matches Vs Trainingcontrasting
confidence: 92%
See 2 more Smart Citations
“…All four cumulative workload measures (i.e., PL, SL, EE, and HFS) were significantly higher in matches compared to training, indicating that matches required higher volumes of both total and high-intensity work. PL•min -1 and SL•min -1 were higher in training, which is in contrast to previous reports of higher measures of work rate in competition compared to training (Allard et al, 2020;. This discrepancy may be reflective of population differences or philosophical differences related to the overall tempo of training design.…”
Section: Matches Vs Trainingcontrasting
confidence: 92%
“…In support of this, despite no differences in total distance covered between positions, forwards competing in elite international U-20 competitions covered significantly greater distances at very fast and sprint speed thresholds, whereas defensemen covered greater distances within very slow, slow, and moderate speeds (Douglas & Kennedy, 2020). Similarly, across an American Hockey League season, forwards performed at a higher relative intensity in matches compared to defensemen, but the total load was similar across positions (Allard et al, 2020). The higher intensity outputs are apparently sufficient to cause forwards to accumulate higher total training volumes and higher work rates, despite the decreased exposure time compared to defensemen.…”
Section: Forwards Vs Defensemenmentioning
confidence: 72%
See 1 more Smart Citation
“…PlayerLoad TM per min has been reported in three of the studies (Douglas et al, 2019b(Douglas et al, , 2020Neeld et al, 2021), however, none of them excluded time on the bench, which makes it challenging to compare this metric to our results. Similar to our study, however solely using the inertial movement unit-device within the Clearsky T6-unit, Allard et al (2020) applied on ice load to quantify external load in a group of fifty male American Hockey League players over an entire season. On ice load was intended to be a more representative and precise measure of PlayerLoad TM in ice hockey, removing all low ACCs (<0.3 m/s −2 ) that typically occur (i.e., time on the bench, substitutions, coasting, gliding, standing, and resting) but at the same time comparable (Pearson correlation: R 2 = 0.98).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of ice hockey match demands has revealed significant differences in intensity distribution between positions, periods, and odd-man situations (Douglas and Kennedy, 2019 ). Typically, forwards cover more distance in high-intensity zones (>17 km/h) compared with defensive players (Lignell et al, 2018 ; Douglas and Kennedy, 2019 ; Allard et al, 2020 ) and both total distance and intensity have been shown to decline from 1st to 3rd period (Brocherie et al, 2018 ; Lignell et al, 2018 ; Douglas and Kennedy, 2019 ; Douglas et al, 2019a ; Allard et al, 2020 ). Interestingly, one study by Douglas et al ( 2019b ) compared the external load difference between training and matches in a group of elite female players.…”
Section: Introductionmentioning
confidence: 99%